A thermodynamic analysis and economic evaluation of an integrated cold-end energy utilization system in a de-carbonization coal-fired power plant. (15th January 2019) - Xu, Cheng; Gao, Yachi; Xu, Gang; Li, Xiaosa; Zhao, Shifei; Yang, Yongping
Highlights: An improved MEA-based de-carbonization coal-fired power plant is proposed. Cold-end energy within reboiler, air and regenerative heaters are redistributed. Exergy destruction within reboiler block and air preheating process are reduced. Efficiency penalty is reduced by 3.2%-points through cold-end energy utilization. The COE and COA of the proposed system are reduced by 8.0% and 22.2%. Abstract: Huge amount of cold-end energy discharged from the CO2 capture/compression process is not thermodynamically satisfactory for monoethanolamine (MEA)-based de-carbonization coal-fired power plants. In this study, an improved cold-end energy utilization concept for a MEA-based de-carbonization coal-fired power plant was innovatively proposed, which highly integrates the CO2 capture/compression, steam bleeding, and boiler air pre-heating processes to cascade utilize the system cold-end energies, and beneficially supplies the heat required for solvent regeneration and air preheating. To be specific, three paths have been adopted: (1) reboiler condensate recirculation: part of the reboiler condensate is recirculated to mix with the steam bleed to provide the heat for solvent regeneration; (2) absorption heat transformer (AHT): upgrading the reboiler condensate heat for solvent regeneration; and (3) multi-stage air heating: cascade utilization of the heat discharged from coolers within CO2 capture/compression process to preheat combustion air prior to the flue gas-air preheater, saving part of the flue gas heat to be used in a more cascade way. The mass and energy balance of the proposed system and the overall system performance were determined using the process simulation. The energy saving mechanism of the adopted three paths were investigated through adopting the graphical exergy analysis for the reboiler block and air preheating process. The cost of electricity (COE) and cost of CO2 avoided (COA) of the proposed system were also determined. Results showed that the energy efficiency of the proposed system could be 3.2 percentage points higher than that of the conventional de-carbonization plant without cold-end energy utilization. The COE and COA of the proposed system were reduced by 8.0% and 22.2%, respectively.